Solve the give equation: 1-(p-2)-[(p-3)-(p-1)]=0

Question

Solve the give equation: 1-(p-2)-[(p-3)-(p-1)]=0

in progress 0
Delilah 2 weeks 2021-11-25T08:31:22+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-11-25T08:32:50+00:00

    Answer:

    sorry don’t know the answer to that question

    Step-by-step explanation:

    hope you understand the equation

    0
    2021-11-25T08:32:58+00:00

    Step-by-step explanation:

    Here,

    1 p + 2 p + 3 p + 1 = 0

    3p + 7 = 0

    3p = 7

    p = 7/3 answer

Leave an answer

Browse

14:4+1-6*5-7*14:3+5 = ? ( )